Upaya Meningkatkan Hasil Belajar Siswa pada Mata pelajaran Pendidikan Agama Islam Melalui Metode Resitasi dan Simulasi di Kelas IV SD Negeri 050578 Kwala Begumit - Zuhaira Zuhaira (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2025)
This study examines the effectiveness of the Recitation and Simulation methods in improving students' learning outcomes in Islamic Education (PAI) at SD Negeri 050578 Kwala Begumit. The research was motivated by the observed low achievement of students, where many did not meet the Minimum Completion Criteria (KKM). A classroom action research (CAR) design was employed, consisting of two cycles, each involving planning, action, observation, and reflection. The findings indicated a significant improvement in cognitive abilities: the average score increased from 43.41% in the pre-cycle to 56.72% in Cycle I, and further to 95.23% in Cycle II. These results demonstrate that the combination of Recitation and Simulation methods effectively enhances students' understanding and engagement, ultimately leading to improved academic performance in PAI.